REMOVAL OF Zn(II) IONS FROM AQUEOUS SOLUTION BY ADSORPTION ON MUSTARD HUSKS - BULGARIU, Dumitru; JURAVLE, Doru Toader; BULGARIU, Laura (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Removal of Zn(II) ions by adsorption on a low-cost material, namely mustard husks, was examined in this study. The batch experiments were performed as a function of initial solution pH, adsorbent dose, initial Zn(II) concentration and contact time, at room temperature (25 ± 0.5°C), in order to establish the optimum conditions of adsorption process. The experimental results have shown that 5.0 g/L of mustard husks is sufficient to remove 73.16% of 54.20 mg/L Zn(II) from 25 mL of aqueous solution, in 60 min of contact time and at initial solution pH of 5.5. The adsorption data fitted well the Langmuir isotherm model, with a maximum adsorption capacity of 12.99 mg/g, while the kinetics of adsorption process is described by pseudo-second order model. The results of this study highlight that the mustard husks can become an efficient and economical alternative for the removal of Zn(II) ions from aqueous effluents.